Identifying Price Informativeness - Dávila, Eduardo; Parlatore, Cecilia (Review of Financial Studies, 2026)
We identify and estimate price informativeness, a necessary step in testing theories of information aggregation. Starting from a pricing equation and a stochastic process for payoffs, we show how to recover relative price informativeness from regressions of asset price changes on changes in payoffs. Applying our identification results, we estimate a panel of stock-specific measures of informativeness for U.S. stocks. In the cross-section, large stocks with high turnover, idiosyncratic volatility, institutional ownership, and analyst coverage have higher informativeness. In the time series, the median, mean, and standard deviation of the distribution of informativeness have steadily increased since the mid-1980s.